2017
DOI: 10.1007/s11144-017-1228-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective hydrogenation of cinnamaldehyde at atmospheric pressure over combustion synthesized Pd catalysts

Abstract: Abstractcovered with alumina layer, bringing in additional stability to the Pd-species in the SCS catalyst and making it highly recyclable. The analogous IWI catalyst, on the contrary, contains a mixed Pd-PdO ensemble that does not increase the stability causing continuous loss of activity in the consecutive cycles of hydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Pd-based catalysts are good for the selective hydrogenation of CAL to HCAL; some representative results are shown in Table . Xu et al, Bakuru et al, and Nagpure et al reported the selective hydrogenation of CAL to HCAL over Pd/OGF (oxygen-functionalized graphite felt), Pd⊂MIL-101­(Fe) MOF, and Pd-NMC (nitrogen-doped mesoporous carbon) catalysts; HCAL selectivities were as high as 92%, 86.4%, and 93%, with complete CAL conversion achieved at 80 °C for 3 h, 40 °C for 1.5 h, and 30 °C for 3 h, respectively.…”
Section: Selective Hydrogenation Of Cal Over Noble Metal Catalystsmentioning
confidence: 99%
“…Pd-based catalysts are good for the selective hydrogenation of CAL to HCAL; some representative results are shown in Table . Xu et al, Bakuru et al, and Nagpure et al reported the selective hydrogenation of CAL to HCAL over Pd/OGF (oxygen-functionalized graphite felt), Pd⊂MIL-101­(Fe) MOF, and Pd-NMC (nitrogen-doped mesoporous carbon) catalysts; HCAL selectivities were as high as 92%, 86.4%, and 93%, with complete CAL conversion achieved at 80 °C for 3 h, 40 °C for 1.5 h, and 30 °C for 3 h, respectively.…”
Section: Selective Hydrogenation Of Cal Over Noble Metal Catalystsmentioning
confidence: 99%
“…S15 and Table S1†). 3,38,39 Pd catalysts commonly thermocatalytically hydrogenate CAL to non-COL products since the hydrogenation of CC is thermodynamically preferred over that of CO. We further conducted the ECH of CAL using a commercial Pd/C catalyst (average particle size: 5 nm). The commercial Pd coated on CF also shows preferred selectivity to the desired COL, although the FE and selectivity were much decreased compared to those of our Pd/CF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S15 and Table S1 †). 3,38,39 Pd catalysts commonly thermocatalytically hydrogenate CAL to non-COL products since the hydrogenation of CvC is thermodynamically preferred over that of CvO. We further conducted the ECH of CAL using a commercial Pd/C catalyst (average particle size: 5 nm).…”
Section: Performance For the Ech Of Calmentioning
confidence: 99%
“…The unsaturated allylic alcohol (UAA) produced through this process is widely utilized as the primary feedstock in food and perfumery industries and intermediates in pharmaceutical industries. 1,2 However, the reaction is classically carried out using gaseous hydrogen in the presence of noble metals as catalysts with significant limitations such as high-pressure requirements and low selectivity to UAA. 3 The high-pressure involved in such a chemical process requires expensive equipment and an elaborate experimental set-up with associated safety risks.…”
Section: Introductionmentioning
confidence: 99%